Wolves and People in Polish-Ruthenian Folk Tales: In the Light of New Perspectivism - Filipowicz, Anna (Literatura Ludowa. Journal of Folklore and Popular Culture, 2024)
Contemporary cultural anthropology, aware of the scale of anthropocentric abuses of the Western relationship between human and nature, is turning towards autochtonous knowledge. Ethnologists find there models of inclusive “being in the world”, which is understood as a system of mutual dependencies and common property of people and animals, including competitive predators (wolves). Pre-Christian European traditions, including native folk culture, also preserved non-anthropocentric representations of the relationship between humans and wolves, visible in some animal and magical folk tales. They raise the problem of mutual coexistence of human and non-human beings and the resulting ethical obligations for humans, close to contemporary ecological postulates